Africa Digest : Trends and issues in macro environment Vol. 21 - Burger, Johan (2020)
The Africa Digest is a e-newsletter scanning the key trends in the macro-environment and industry to promote knowledge and raise understanding of business in Africa. This issue explores: 1. Developments in Agriculture - Food production in Africa continues to be a high priority for government leaders, leading to a range of initiatives to stimulate the horticulture sector. Specific sub-sectors are now in sharper focus. 2. Digital and Mobile Money Developments - Africa has been developing its mobile money opportunities with enthusiasm since the start of M-Pesa in 2007. Given the large portion of the population that is unbanked, the opportunities are vast. To increase the level of financial inclusivity, regulators are embracing non-traditional financial services entities such as telecommunications companies to help address this challenge. 3. Developments in the Manufacturing Sector - For many years, South Africa dominated Africa’s automobile sector. In the past few years, Morocco took the mantle of the dominant car producer on the African continent. However, major manufacturers are expanding their assembly facilities to a number of other countries in Africa. The sector faces a number of challenges, one of which is access to financing of new cars. 4. Developments in Renewable Energy - Africa sees a healthy increase in development of renewable energy projects. Solar, wind, geothermal and hydro projects are under construction all over the continent. 5. Developments in Sustainability - Africa increasingly develops innovative ways to address challenges such as plastic waste pollution, deforestation, waste-water problems and invasive weeds.